Context matters: A community-based study of urban minority parents’ views on child health - Bolar, Cassandra L. (J Ga Public Health Assoc, 2016)
BACKGROUND: Among children, there are substantial ethno-racial minority disparities across a broad range of health-related behaviors, experiences, and outcomes. Addressing these disparities is important, as childhood and adolescence establish health trajectories that extend throughout life. METHODS: The current study employed a community-based participatory research approach to gain community insight on child health priorities and to frame an intervention aimed at improving the health of minority children. Eight focus groups were conducted among seventy-five African American parents in a Southeastern city. The current study was guided by an ecological theoretical framework. RESULTS: Although the focus of this investigation was on community identification of child health priorities, participants cited, as root determinants, contextual factors, which included lack of healthy food options, lack of spaces for physical activity, and community violence. These co-occurring factors were related to limited engagement in outdoor activities and physical activity, increased obesity, and poor mental health and coping. Poor parenting was cited as the most substantial barrier to improving child health outcomes, and quality parenting was identified as the most important issue to address for community programs focused on promoting the health and success of children. For improving health outcomes for children in their neighborhoods, establishment of positive social capital and constructive activities were also cited. CONCLUSIONS: These results reinforce social determinants of health as influences on child health outcomes and describe how community engagement can address potential solutions through interventions that resonate with program participants.